Harnessing the Synergistic Interplay of Fischer‐Tropsch Synthesis (Fe‐Co) Bimetallic Oxides in Na‐FeMnCo/HZSM‐5 Composite Catalyst for Syngas Conversion to Aromatic Hydrocarbons. Issue 8 (23rd February 2021) - Nawaz, Muhammad Asif; Li, Minzhe; Saif, Maria; Song, Guiyao; Wang, Zihao; Liu, Dianhua
Abstract: The efficient conversion of syngas to aromatic hydrocarbons (STA) has attracted attention in recent years for its extensive utilization in the energy and defense sectors. In current study, the alloying of two active FT synthesis metal components (Fe−Co) was employed in Na‐FeMnCo/HZSM‐5 composite catalyst for STA process. Different calcination temperatures and Fe/Mn/Co molar ratios were modulated for harnessing the different Fe2 O3 /CoFe2 O4 /MnCo2 O4 structures that possessed divergent structural, reduction, carburization and catalytic behaviors to give Fe3 O4 /Fex C/Cox C reactive species. Herein, the effective inclusion of Co and Mn into Fe brought about the expedient geometric and electronic modulations for providing the homogenously distributed CoFe2 O4 nanocrystals. This particular substitution of Fe played a vital role for tuning the density of oxygen vacancies, tailoring the reduction behavior of Fe‐Ox, giving the Fe−Co alloy structure, and adjusting the adsorption capabilities of catalytic surface that mainly dictate the concentration of active Fe5 C2 phase. An escalated selectivity to olefinic intermediates and subsequent higher aromatics fractions (∼55 %) thus was imparted with an inhibited CO2 (21 %) generation by meliorating the different Fischer‐Tropsch/Aromatization reactions in stable CO conversion of ∼98 %. Abstract : Harnessing the power of change : Tuning the substitution of different Fe2 O3 /CoFe2 O4 /MnCo2 O4 structures allowed for divergent textural, structural, reduction, carburization and catalytic behaviors. Remarkable catalytic activity was imparted by meliorating the fraction of lower olefinic intermediates being subsequently adsorbed on zeolite surface and transformed into ∼55 % selectivity of desired aromatic hydrocarbons.